Photodynamic therapy with hematoporphyrin derivative for the treatment of penile verrucous carcinoma: A case report - Runqun Liu; Xiaoqing Xiang; Yanliang Li; Guozhang Ma; Junhong Ye (Photodiagnosis and Photodynamic Therapy)
Verrucous carcinoma, a well-differentiated variant of squamous cell carcinoma with low-grade malignancy, is often associated with localized human papillomavirus (HPV) infection and excessive penile foreskin. We report a 45-year-old male who presented with a verrucous plaque on the glans penis for over four months, along with itching. Examination revealed a verrucous, erosive lesion with a cauliflower-like surface, firm texture, and irregular shape, accompanied by pain, bleeding, and a foul odor. Syphilis and HIV tests were negative, and a biopsy confirmed verrucous carcinoma.The patient underwent initial circumcision at a local hospital, but persistent lesions raised concerns about further surgery impairing sexual function and anatomical integrity. To preserve both anatomical and functional integrity, the patient opted for Hematoporphyrin Derivative-Photodynamic Therapy (HpD-PDT). Post-treatment, the lesions regressed, and after four years of follow-up, there was no scarring or recurrence. The clinical outcome was favorable with complete lesion regression.We propose that PDT is a viable treatment option for penile verrucous carcinoma, offering advantages over traditional methods in terms of function preservation and cosmetic outcomes.